2016
DOI: 10.1089/chi.2015.0212
|View full text |Cite
|
Sign up to set email alerts
|

Well Baby Group Care: Evaluation of a Promising Intervention for Primary Obesity Prevention in Toddlers

Abstract: WBG, a replicable model integrated into primary care visits, affords a unique opportunity to intervene consistently and early, providing families in at-risk communities with increased provider time, intensive education, and ongoing support. Further study of group well-child care for primary obesity prevention is warranted to confirm the effectiveness of the model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(86 citation statements)
references
References 36 publications
0
85
1
Order By: Relevance
“…Repeated reinforcement of key messages, practicing new skills, and providing long‐term support may change women's efficacy and outcome expectancies and therefore help some women adopt and sustain healthy improvements in a diverse range of health behaviors. These strategies may be effective; participation in the group well‐baby care arm was associated with an 88% reduction (adjusted odds ratio, 0.12; 95% CI, 0.02‐0.93; P = .04) in the risk of toddlers being overweight or obese at age 2 years in a recent study of our model of care (N = 47) …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Repeated reinforcement of key messages, practicing new skills, and providing long‐term support may change women's efficacy and outcome expectancies and therefore help some women adopt and sustain healthy improvements in a diverse range of health behaviors. These strategies may be effective; participation in the group well‐baby care arm was associated with an 88% reduction (adjusted odds ratio, 0.12; 95% CI, 0.02‐0.93; P = .04) in the risk of toddlers being overweight or obese at age 2 years in a recent study of our model of care (N = 47) …”
Section: Discussionmentioning
confidence: 99%
“…Group prenatal care and group well‐baby care are promising strategies for better addressing family needs and improving clinical and social outcomes. Studies to date have shown that the immediate outcomes associated with group prenatal and well‐baby care are at least as good, if not better, than those associated with individual care and include greater satisfaction, higher breastfeeding initiation rates, lower rates of preterm birth, and lower rates of overweight and obesity in children participating in group pediatric care at 15 months and 24 months . However, whether the knowledge and skills gained in group prenatal or group well‐baby care are used long term is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the greatest opportunity for obesity prevention is in early life before behavioural patterns are established. Programs to prevent the development of obesity have had variable success . Recent reviews described the paucity of effective obesity prevention programs and obesity prevention studies for children under the age of 3 years …”
Section: Introductionmentioning
confidence: 99%